2018
DOI: 10.5935/1980-6906/psicologia.v20n1p47-60
|View full text |Cite
|
Sign up to set email alerts
|

Emotional aspects present in the lives of amputees: a literature review

Abstract: Sistema de avaliação: às cegas por pares (double blind review).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 16 publications
3
7
0
11
Order By: Relevance
“…But long after surgery, patients, in addition to physical and mental suffering, face a number of difficult problems: the cost of the prosthetic limb, the pursuit of compensation in the case of car or work-related accidents, continuing treatment for chronic disease (such as diabetes), decreased sexual activity, especially in young people, and, in particular, uncertainty about the future. The latter is the most commonly reported feeling (Galván et al, 2009;Sales et al, 2012;Simsek et al, 2017;Bergo and Prebianchi, 2018) and it was also present in the findings of our study. It stands to reason that in order for the person to regain a sense of normality and to be able to develop an adaptive new self-representation as a participative active being in the environment, a complex system of support and resources must be in place.…”
Section: In or Outsupporting
confidence: 88%
See 4 more Smart Citations
“…But long after surgery, patients, in addition to physical and mental suffering, face a number of difficult problems: the cost of the prosthetic limb, the pursuit of compensation in the case of car or work-related accidents, continuing treatment for chronic disease (such as diabetes), decreased sexual activity, especially in young people, and, in particular, uncertainty about the future. The latter is the most commonly reported feeling (Galván et al, 2009;Sales et al, 2012;Simsek et al, 2017;Bergo and Prebianchi, 2018) and it was also present in the findings of our study. It stands to reason that in order for the person to regain a sense of normality and to be able to develop an adaptive new self-representation as a participative active being in the environment, a complex system of support and resources must be in place.…”
Section: In or Outsupporting
confidence: 88%
“…This study confirms the meta-analysis of Bergo and Prebianchi (2018) who, quoting Rodrigues (2011) , concluded that the emotional responses following amputation differ from patient to patient, and are influenced by a constellation of factors: the etiology of amputation, elements of personal life, the social-historical moment, the pathogenicity of the disease, and the patient’s interpretation of the symptoms. Patients who suffer from amputation due to a vascular disorder that causes unbearable pain will feel relieved.…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations